Nerve Growth Factor Enhances Tooth Mechanical Hyperalgesia Through C-C Chemokine Ligand 19 in Rats - Guo, Rui; Chen, Yiyin; Liu, Lu; Wen, Jing; Yang, Hong; Zhu, Yafen; Gao, Meiya; Liang, Hengyan; Lai, Wenli; Long, Hu (Frontiers in Neurology, 2021)
The nerve growth factor (NGF) plays an important role in the regulation of neuropathic pain. It has been demonstrated that calcitonin gene-related peptide (CGRP), a well-known contributor to neurogenic inflammation, increases neuroinflammatory pain induced by NGF. The inflammatory mediator that NGF most strongly induces is C-C chemokine ligand 19 (CCL19), which can recruit inflammatory cells by binding to the receptor CCR7 followed by promoting the response of neuroinflammation. However, the regulatory mechanism of NGF and CCL19 in tooth movement orofacial pain and the interaction between both are still unclear. In this study, male Sprague–Dawley rats were used to study the modulation of NGF on orofacial pain through CCL19 and the role of each in tooth movement pain in rats. The expression levels of CCL19 mRNA and protein were determined by real-time PCR and immunofluorescence, respectively. Pain levels were assessed by measuring the rats' bite force, which drops as pain rises. Meanwhile, by verifying the relationship between CGRP and CCL19, it was laterally confirmed that NGF could modulate tooth movement-induced mechanical hyperalgesia through CCL19. The results showed that the expression level of CCL19 rose with the increased NGF, and neurons expressing CGRP can express stronger CCL19. Compared with the baseline level, the bite force for all rats dropped sharply on day 1, reached its lowest level on day 3, and recovered gradually on day 5. All results indicated that NGF played an important role in tooth movement orofacial pain via positively regulating CCL19 expression in the trigeminal ganglia of rats. Additionally, CCL19 increased the sensitivity to experimental tooth movement orofacial pain. NGF can regulate CCL19 expression, although it may regulate other inflammatory pathways as well. This is the first report on the interactions and modulations of tooth movement orofacial pain by NGF through CCL19 in rats.